Providing Quality of Life on the Basis of Quality of Public Administration Improvement - Vladimir Valentinovich Okrepilov (Управленческое консультирование)
The article considers the Quality of life dependence of the quality of public governance. In this view the author examines various ways of improving the quality of activities carried out by the public authorities through the application of modern quality management methods. The content of standards aimed at facilitation of the quality management systems implementation in state and municipal authorities is analyzed. The article specifies new quality management principles developed taking into account the specifics of the public authorities’ activities. The author considers various self-assessment models, including the one aimed for the state authorities, as well as the assessment model for rating the public authorities’ activities of foreign countries.